The Relationship Between Knowledge Level and Attitudes of Mothers of Toddlers Towards Visits to Posyandu In Janti Village, Tarik District, Sidoarjo - Sutatik, Yuning; Wittiarika, Ivon Diah; Djuari, Lilik (Jurnal Kebidanan Midwiferia, 2024)
One of the objectives of the Posyandu program is to reduce nutritional problems. The rate of malnutrition in Sidoarjo Regency is 3.8%, at the Tarik Health Center it is 0.13%, and in Janti Village, it reaches 5.13%. Malnutrition negatively impacts toddler growth. In 2023, the visit rate of toddlers to Posyandu in Janti Village was low, at only 32.1% of the total number of toddlers in the village, resulting in suboptimal monitoring of their growth. One factor influencing mothers' visits to Posyandu is their knowledge and attitude.This research is an analytical observational study with a cross-sectional design, aiming to analyze the relationship between the knowledge and attitudes of mothers of toddlers towards visits to Posyandu in Janti Village, Tarik District, Sidoarjo. The population consisted of 224 mothers of toddlers, with a sample of 70 respondents selected randomly through random sampling. Data were collected through questionnaires on the knowledge and attitudes of mothers towards Posyandu, as well as attendance records at Posyandu, and analyzed using Chi-Square and Fisher's Exact tests.Most respondents were aged 25-34 years (72.9%), had completed high school education (50.5%), and were housewives (62.6%). They generally possessed good knowledge about Posyandu (68.6%) or adequate knowledge (31.4%). Regarding visitation, 64.3% were active and 35.7% were inactive. This suggests that positive knowledge and attitudes towards Posyandu significantly influence visitation rates, supported by statistically significant results with a p-value of 0.001 (≤ 0.05).There exists a relationship between the level of knowledge and attitudes of mothers towards visits to Posyandu.